Risk factor of severe diarrhea and enterocolitis induced by CAPOX: a retrospective multicenter study - A. Teixeira; T. Felismino; M.D. Donadio; G. Catani; A.L.M. da Silva; R. Weschenfelder; R.D. Peixoto; J.M. O’Connor; A.K. Coutinho; R.P. Riechelmann (ESMO Gastrointestinal Oncology)
Background: We have previously suggested that concurrent use of capecitabine plus oxaliplatin (CAPOX) and angiotensin receptor blockers (ARBs) significantly increased the risk of severe diarrhea and/or enterocolitis. We conducted a multicenter larger study to validate this finding, adjusting for other risk factors. Patients and methods: This was a retrospective multicenter study of patients with colorectal cancer treated with at least one cycle of CAPOX. The primary endpoint was grade (G) ≥3 diarrhea and/or enterocolitis induced by CAPOX. Unadjusted and adjusted logistic regression models were used to evaluate risk factors for G ≥3 diarrhea and/or enterocolitis. P < 0.05 was deemed significant. Results: From April 2010 to December 2023, 362 patients were included. In univariate analyses, age ≥65 years, right-sided tumors, use of ARBs or angiotensin-converting enzyme inhibitors (ACEi), age-adjusted Charlson Comorbidity Index, and estimated glomerular filtration rate (eGFR) <60 ml/min were associated with G ≥3 diarrhea and/or enterocolitis. In the multivariable analysis, age ≥65 years [odds ratio (OR) 2.71, 95% confidence interval (CI) 1.38-5.33, P = 0.004] and eGFR <60 ml/min (OR 5.4, 95% CI 2.25-13.8, P < 0.001), but not use of ARBs or ACEi, were significant. Conclusions: Age ≥65 years and eGFR <60 ml/min were independent risk factors for G ≥3 diarrhea/enterocolitis in patients treated with CAPOX. Concurrent use of ARBs or ACEi was not associated with G ≥3 diarrhea/enterocolitis.